Characterization of porin and ompR mutants of a virulent strain of Salmonella typhimurium: ompR mutants are attenuated in vivo. - Dorman, C J (1989)
The ompC, ompD, and ompF genes encode the three major porins of Salmonella typhimurium. ompR encodes a positive regulator required for the expression of ompC and ompF. Transposon-generated mutations in ompC, ompD, ompF, and ompR were introduced into the S. typhimurium mouse virulent strain SL1344 by P22-mediated transduction. Following preliminary characterization in vitro, the strains were used to challenge BALB/c mice by using the oral or intravenous route. Strains harboring ompC or ompF mutations were as virulent as SL1344 after oral challenge. Strains harboring ompD mutations had a slight reduction in virulence. In contrast, ompR mutants failed to kill BALB/c mice after oral challenge and the intravenous 50% lethal dose was reduced by approximately 10(5). The ompR mutants persisted in murine tissues for several weeks following oral or intravenous challenge. Furthermore, mice orally immunized with these ompR mutant strains were well protected against challenge with virulent SL1344.